Efficient hybrid flooding scheme for ad-hoc on-demand distance vector routing protocol in MANET - Waheed, Bassam M.S. (2014)
A mobile ad-hoc network (MANET) consists of multiple wireless mobile nodes that can freely and dynamically organize themselves into arbitrary and temporary network topologies, enabling users and devices to seamlessly internetwork in areas without aid of any established infrastructure or centralized administration. Efficacious routing among set of mobile nodes is one of the most important activities in MANETs. Existing on-demand routing protocols perform route discovery process by flooding the network with a query message (RREQs) requesting a route to the destination. As flooding involves querying all reachable network nodes, frequent flooding can rapidly deplete the energy reserved at each node, in addition to consuming significant portion of the available network bandwidth. Further, as the number of communicating nodes increases, more congestion and collisions can be expected leading to what is known a broadcast storm problem. Many approaches have been developed to resolve the broadcast storm problem; some of them were based on developing a virtual backbone that takes the responsibility of forwarding control packets with the wireless ad-hoc network, where only nodes that recognize themselves as gateways will forward the RREQ packets. An example of such approach is the Connected Dominating Set (CDS). The dominating-set-based routing is a promising approach, where the searching space for a route is reduced to nodes in the set. Another prominent approach is the Dominant Pruning (DP) which is a distributed dominating set algorithm developed to alleviate the impact of flooding in mobile ad-hoc networks. Both dominant pruning and connected dominating set require 2-hop neighbor information. This information can be collected with the aid of neighbor protocol. In this thesis an enhanced neighbor protocol (ENP) has been developed to collect and maintain 2-hop neighbor information at each node. Neighbor information is essential for guiding the hosts in determining their status if they are gateway hosts or not. The protocol is a distance-based one, which depends on the change in the nodes geographic location to make them exchange their neighbor information. Thresholds selection is based on three performance metrics namely: maintenance overhead, number of times the links break and data delivery ratio. These metrics often conflict against each other in trying to achieve the most optimum threshold distance. Therefore, a trade-off is needed to obtain fair threshold values between them. The other optimization in this thesis is the handling of unidirectional links between nodes in MANET. In this context, the algorithm responsible for determining whether or not the a node is gateway is adapted to check for such links, this is done by looking for mutual existence of nodes in the neighbor tables of their respective neighbors. Finally, focus is given to the routing cost reduction through the incorporation of Dominant Pruning (DP) as assisting factor that works together with the constructed Connected Dominating Set (CDS). Thus, a hybrid flooding scheme is obtained which combines sender and -receiver-based schemes. The benefit is to reduce the length of paths between the source and destination nodes by providing more options for the flooded packets while they travel in the network. To show the benefit of the ENP protocol, it has been utilized as the neighbor protocol with the CDS and both are integrated into AODV routing protocol. ENP performance is compared against the original neighbor protocol of the CDS, DP and the periodic approach followed by the AODV. To evaluate CDS performance for unidirectional links, both original and enhanced marking process, are incorporated separately into AODV. Simulation results show that CDS generated by the enhanced marking process exhibits better data delivery rate and lower link broke count than CDS generated by the original marking process. Finally, in terms of routing cost reduction, the hybrid flooding scheme is incorporated into AODV to evaluate its benefits. The scheme showed better data delivery and lower average-end-to-end delay with good flooding efficiency. All the simulations mentioned above have been carried out with QualNet version 5.02 from Scalable Networks Technologies.